¿Cómo se duerme a un bebé en la Amazonía? Apropiación del villancico chachapoyano Niño Manuelito como canto de cuna en varios grupos de la red Ucayali-Amazonas - Alejandro Prieto Mendoza (Journal de la Société des Américanistes)
In this article, I argue that the lullabies of shipibo-konibo, kakataibo, amahuaca, kukama, yagua, and magütá mothers share a series of features. The melody is based on the Chachapoyan Christmas carol Niño Manuelito and the texts are adapted to the melody by a hexasyllabic line or by vowel lengthening and deletion. Mothers sing in high register, use falsetto voice, and employ a voice bilabial trill to sing the melody. Quechuisms are used, specifically waka “cow” is associated with the action of eating the baby or wawa. I propose that the carol Niño Manuelito circulated in the Ucayali-Amazonas network due to Franciscan missionary work and forced migrations during the first rubber boom (1879-1912); in turn, the melody was reinterpreted as a lullaby and then spread throughout this river network and adapted to the characteristics of the song present in the region. Finally, I discuss a second type of common traits proper of the lullaby as a musical genre such as diminutives, reduplications, the topic of a potential danger, and repetitions.